2008
DOI: 10.1029/2008ja013157
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric amplification and emission triggering by ELF/VLF waves injected by the 3.6 MW HAARP ionospheric heater

Abstract: [1] The HF dipole array of the High Frequency Active Auroral Research Program (HAARP) in Gakona, Alaska, was recently upgraded to 180 elements, facilitating operations at a total radiated power level of 3.6 MW and an effective radiated power of $575 MW. In the first experiments at the new power level, the HAARP array is used for magnetospheric wave injection. Modulated heating of auroral electrojet currents in the ionosphere yields radiation in the ELF/VLF frequency range. The HAARP-generated signals are injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…Therefore, the mark on the spectrogram in Figure 2 (bottom) near 22:43:02 UT (inside the dashed box) is the amplified signal with the 6′ frequency‐time format transmitted by HAARP during the previous 1 min of the experiment. Although at the time of the observations Tangaroa was south of the HAARP conjugate point at a higher L shell than HAARP (see Table 1), it is assumed that the signals traversed the magnetosphere on L shells close to that of the HAARP facility as was found in previous HAARP wave injection experiments [ Inan et al , 2004; Gołkowski et al , 2008, 2009, 2010].…”
Section: Observationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the mark on the spectrogram in Figure 2 (bottom) near 22:43:02 UT (inside the dashed box) is the amplified signal with the 6′ frequency‐time format transmitted by HAARP during the previous 1 min of the experiment. Although at the time of the observations Tangaroa was south of the HAARP conjugate point at a higher L shell than HAARP (see Table 1), it is assumed that the signals traversed the magnetosphere on L shells close to that of the HAARP facility as was found in previous HAARP wave injection experiments [ Inan et al , 2004; Gołkowski et al , 2008, 2009, 2010].…”
Section: Observationsmentioning
confidence: 94%
“…This paper presents results from a detailed, numerical study of the propagation of whistler mode waves transmitted by the High Frequency Active Aurora Research Program (HAARP) facility in Gakona, Alaska. The HAARP facility is an ionospheric heater that is able to generate extremely low frequency (ELF)/very low frequency (VLF) waves by modulating the ionospheric conductivity in the D region and thus modify the auroral electrojet currents [ Papadopoulos et al , 2003; Gołkowski et al , 2008; Cohen et al , 2008]. In the absence of conventional transmitters in the ELF/VLF: 500 Hz to 8 kHz band (Siple Station was discontinued in 1988), HAARP provides a unique platform for controlled wave injection studies.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the HAARP near‐field phased‐array HF facility near Gakona, Alaska (62° 22′ N, 145° 9′ W), has been used to generate ELF/VLF signals that have been observed as far as 4400 km [ Moore et al , 2007; Cohen et al , 2010c], as well as injected into the magnetosphere and observed in the geomagnetic conjugate region [ Inan et al , 2004; Gołkowski et al , 2008, 2011]. In 2007, an upgrade of HAARP was completed, increasing its capacity from 48 active elements, 960 kW input power, and 175 MW ERP (at 3.25 MHz), to 180 active elements, 3.6 MW input power, and ∼400 MW ERP (at 3.25 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the most efficient methods described in the literature include "beam painting" and geometric modulation techniques. The injection of extremely-low frequency (ELF)/very-low frequency (VLF) waves into the magnetosphere by the modulated heating of the electrojet by the High Altitude Active Research Program (HAARP) facility in Alaska has been extensively studied by Papadopoulos et al (2003), Golkowski et al (2008, 2011), and Cohen et al (2010. The entire process is modulated with the frequency of the generated wave.…”
Section: Introductionmentioning
confidence: 99%